Sub Bagian Peranan Informasi dan Hubungan Masyarakat terhadap Kinerja Pegawai di Kantor Wilayah Kementerian Agama Provinsi Sumatera Utara - Irfan Iskandar; Muhamad Arif (JURNAL RISET MANAJEMEN (JURMA), 2024)
Civil servants as apparatus resources are required to have high and professional knowledge, abilities and expertise because of their position as one of the elements of the state apparatus, servants of the state and servants of the community who play a very strategic role and development tasks. Organizational effectiveness is greatly influenced by individual effectiveness, so that low employee performance also affects the low performance of the Regional Office of the Ministry of Religion of North Sumatra Province as a whole. The problem raised in this study is how the role of Public Relations in processing information to the public at the regional office of the Ministry of Religion of North Sumatra Province. The method used in this research is descriptive analysis using a qualitative approach, the Public Relations Division in the North Sumatra Regional Office of the Ministry of Religion plays an important role in providing information to the public. Therefore, researchers suggest the need to improve facilities in order to support the work in the Public Relations section in the regional office of the Ministry of Religion prov. North Sumatra and build good communication, and it is also important to add personnel who are experts in this field, so that the information provided to the public can be maximized and more varied.